Comments on the Proposed Pediatric Oral Health Therapist - James B. Bramson, DDS; Albert H. Guay, DMD (Blackwell Synergy, 2005)
A recent article in the Journal of Public Health Dentistry, Developing and Deploying a New Member of the Dental Team: A Pediatric Oral Health Therapist (2005 65:48-55), written by David A. Nash, DMD, MS,EdD, proposed the development of a lower level practitioner as a dentist-substitute for the provision of caries treatment for children as means of addressing ÃƒÂ¢Ã¢â€šÂ¬Ã‚Âthe significant disparities in oral health that exist among children in the United StatesÃƒÂ¢Ã¢â€šÂ¬Ã‚Â (1).